Novel splice site mutation in the growth hormone receptor gene in Turkish patients with Laron-type dwarfism - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2008)
Growth hormone (GH) is involved in growth, and fat and carbohydrate metabolism. Interaction of GH with the GH receptor (GHR) is necessary for systemic and local production of insulin-like growth factor-I (IGF-I) which mediates GH actions. Mutations in the GHR cause severe postnatal growth failure; the disorder is an autosomal recessive genetic disease resulting in GH insensitivity, called Laron syndrome. It is characterized by dwarfism with elevated serum GH and low levels of IGF-I. We analyzed the GHR gene for mutations and polymorphisms in eight patients with Laron-type dwarfism from six families. We found three missense mutations (SOL, V125A, 1526L), one nonsense mutation (W157X), and one splice site mutation in the extracellular domain of GHR. Furthermore, G168G and exon 3 deletion polymorphisms were detected in patients with Laron syndrome. The splice site mutation, which is a novel mutation, was located at the donor splice site of exon 2/ intron 2 within GHR. Although this mutation changed the highly conserved donor splice site consensus sequence GT to GGT by insertion of a G residue, the intron splicing between exon 2 and exon 3 was detected in the patient. These results imply that the splicing occurs at the GT site in intron 2, leaving the extra inserted G residue at the end of exon 2, thus changing the open reading frame of GHR resulting in a premature termination codon in exon 3.
Keywords: growth hormone receptor; Laron syndrome; short stature; PITUITARY DWARFISM; INSENSITIVITY; CHILDREN; DOMAIN; DNA